Red Light-Initiated Cross-Linking of NIR Probes to Cytoplasmic RNA: An Innovative Strategy for Prolonged Imaging and Unexpected Tumor Suppression - Ye, Shuyue; Cui, Chaoxiang; Cheng, Xiaju; Zhao, Meng; Mao, Qiulian; Zhang, Yuqi; Wang, Anna; Fang, Jing; Zhao, Yan; Shi, Haibin (Journal of the American Chemical Society, 2020)
Improving the enrichment of drugs or theranostic agents within tumors is very vital to achieve effective cancer diagnosis and therapy while greatly reducing the dosage and damage to normal tissues. Herein, as a proof of concept, we for the first time report a red light-initiated probe-RNA cross-linking (RLIPRC) strategy that can not only robustly promote the accumulation and retention of the probe in the tumor for prolonged imaging but also significantly inhibits the tumor growth. A near-infrared (NIR) fluorescent probe f-CR consisting of a NIR dye (Cyanine 7) as a signal reporter, a cyclic-(arginine-glycine-aspartic acid) (cRGD) peptide for tumor targeting, and a singlet oxygen (1O2)-sensitive furan moiety for RNA cross-linking was rationally designed and synthesized. This probe possessed both passive and active tumor targeting abilities and emitted intense NIR/photoacoustic (PA) signals, allowing for specific and sensitive dual-modality imaging of tumors in vivo. Notably, probe f-CR could be specifically and covalently cross-linked to cytoplasmic RNAs via the cycloaddition reaction between furan and adenine, cytosine, or guanine under the oxidation of 1O2 generated in situ by irradiation of methylene blue (MB) with 660 nm laser light, which effectively blocks the exocytosis of the probes resulting in enhanced tumor accumulation and retention. More excitingly, for the first time, we revealed that the covalent cross-linking of probe f-CR to cytoplasmic RNAs could induce severe apoptosis of cancer cells leading to remarkable tumor suppression. This study thus represents the first red light-initiated RNA cross-linking system with high potential to improve the diagnostic and therapeutic outcomes of tumors in vivo.